(untitled) (Constructionism Conference Proceedings, 2025)
Let’s discover tonal sounds around us and embark on a sampling safari scavenging kitchen utensils (glasses, bottles, spoons, pots, kettles), office supplies (pencil sharpeners, papers ripping, bursting bags) and our bodies’ (in-)voluntary utterances (whistling, wheezing, sneezing, snipping, rasping, cracking, coughing, clapping) – and then turn them into beautiful melodies! We’ll explore various sampling rates to play back recordings at different pitches and learn how to use the algorithm of the Equal Temperament Chromatic Scale to synthesize them into musical tunes. Then we’ll figure out how to mathematically transform the waveform of our recordings into musical scales of semitones by stretching and compressing the sampled data and use this technique to compute personalized ringtones for our phones.